Korelasi Sistem Pemberian Insentif dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Pekerjaan Umum Penataan Ruang dan Perumahan Rakyat Pemerintah Provinsi Kalimantan Timur - Rinda Sandayani Karhab; Vera Anitra; Annisa Hasya Hifdzaniy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the correlation between the incentive system and work discipline on employee performance at the Public Works, Spatial Planning, and Public Housing Department of East Kalimantan Province. The research method used is quantitative, with data collected through questionnaires distributed to 170 employees. Validity and reliability tests showed that the research instruments were valid and reliable. Data analysis was performed using multiple linear regression. The results indicated that both partially and simultaneously, the incentive system and work discipline significantly affect employee performance. The independent variables contributed 14.1% to employee performance, while the remaining 85.9% is influenced by other variables outside this study. This study recommends that management continue to enhance aspects of discipline, cooperation, and employee productivity to improve overall performance .